ALLELOPATHIC POTENTIAL OF ECHINOCHLOA CRUS-GALLI (L.)P. BEAUV. EXTRACTS ON GROWTH AND DEVELOPMENTAL CHANGES OF ABELMOSCHUS ESCULENTU S (L.) AND SOLANUM LYCOPERSICUM (L.) - G.S. REKHA, P. LEELA,; ARUMUGAM, K. (Journal of Plant Stress Physiology)
The study was designed to evaluate the growth and developmental changes of bhendi (Abelmoschus esculentus L. - cv. CO-1) and tomato (Solanum lycopersicum L.- cv. PKM-1) seedlings by using different concentrations of (2g/l, 5g/l, 10g/l, 15g/l and 25g/l) aqueous Echinochloa crus-galli (L.) extracts under pot culture experiments. Barnyard grass extracts showed an inhibitory and stimulatory effects on germination, seedling length, biomass, pigments and biochemical constituents of bhendi and tomato. The 2g/l concentration of extract stimulated the seed germination, seedling growth, biomass and biochemical constituents of bhendi and tomato. The higher concentrations (15g/l and 25g/l) showed an inhibitory effects in all the parameters studied in the two economically important vegetable crops. The degree of retardation was dependent on the concentration gradient of the barnyard grass extracts. Root length, Shoot length, Biomass and Biochemical constituents of tomato seedlings were highly reduced at 25g/l concentrations of aqueous leaf extracts of barnyard grass. Between bhendi and tomato seedlings, more allelopathic influence was observed in tomato than bhendi seedlings.